Building Defects and Facility Maintenance Practices (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
Cracks, rusty surfaces, missing ceiling panels, and moisture issues are common defects in buildings. Insufficient building maintenance will result in serious defects and more expensive repair work. In Malaysia, buildings are constructed under rigorous supervision and in compliance with British Standards. Unfortunately, the building's maintenance elements are still inadequate. Therefore, the main objective of this research is to identify the building defects and provide solutions to them. This research focused on one block from six blocks in Kampung Siswa (Kamsis). Block V1 was selected to investigate the building defects occurring there. The data were collected through questionnaires to evaluate the building defects. 118 respondents were involved from 172 populations. The finding of this study shows crack is the highest score (4.39) and is considered as the main defect that occurred on the Kamsis building. From the data respondents agreed the recommendation is the management service should be improved (4.38). The building defects that occurred will turn to high maintenance cost. It can be concluded that the most common building defects occurring are cracks.